Immediate breast reconstruction with latissimus dorsi flap for patients with local recurrence of breast cancer. Issue 6 (June 2020) - De Lorenzi, F.; Corso, G.; Botta, F.; Invento, A.; Marchetti, A.; Sala, P.; Vottero, G.; Bagnardi, V.; Leonardi, C.; Veronesi, P.; Goldhirsch, A.
Abstract: Background: Ipsilateral breast cancer recurrence (IBTR) occurs in about 7% of patients with primary invasive breast tumor. Salvage mastectomy and breast reconstruction are often discussed and latissimus dorsi (LD) flap is frequently proposed. Methods: We retrospectively investigated 111 consecutive locally relapsing patients who underwent salvage mastectomy and immediate LD reconstruction. All included patients with IBTR previously underwent conserving surgery for BC, and received a postoperative irradiation. Primary endpoints were disease free survival and overall survival. Secondary endpoints were surgical complications and re-interventions. Results: Invasive ductal cancer was the most frequent histotype (60.4%) of breast cancer reappearance. rpT1, rpT2 and rpT3 were observed respectively in 50.5%, 20, 7% and 3, 6% of the patients. rpTis occurred in 11, 7% of cases. Positive axillary nodes were observed in 9, 9% of patients at reappearance. Post-operative complication other than seroma occurred in 17, 1% of patients, while seroma at the donor site was observed in 61.3% of cases. At 5-year after surgery overall survival was 92% (95% CI: 85%–96%) and disease free survival was 78% (95% CI: 69%–85%). Conclusions: Immediate latissimus dorsi flap reconstruction in selected patients with isolated breast tumor recurrence, which occurred after breast irradiation, provides an effective treatment with a satisfactory outcome.